Erich Marckhl - Musikausbildung in der Steiermark nach 1945 : Brüche und Kontinuitäten - Kogler, Susanne (2022)
This volume brings together texts produced as part of a research project funded by the Austrian National Bank (ÖNB) Jubilee Fund, which examined the development and interaction of all the institutions responsible for music education in Styria after 1945: the reorganisation of the music school system, the reopening of the Provincial Conservatory and its transformation into the Academy of Music and Performing Arts. The focus is on the work of Erich Marckhl (1902-1980), who held leading positions in all areas.